Humoral and Cellular Immune Responses to SARS-CoV-2 in Participants with Head and Neck Cancer - Luminita Mărutescu; Alexandru Enea; Nefeli-Maria Antoniadis; Marian Neculae; Diana Antonia Costea; Marcela Popa; Elena Dragu; Elena Codrici; Violeta Ristoiu; Bianca Galateanu; Ariana Hudita; Gratiela Gradisteanu Pircalabioru; et al. (Viruses)
Background: SARS-CoV-2 immunity is understudied in cancer patients. Here, we monitored natural/vaccine-induced SARS-CoV-2 immunity in patients with head and neck cancer (HNC) stratified as vaccinated (mRNA/adenovirus-based vaccines), convalescent, and hybrid immunity. Methods: Plasma/PBMC samples were collected from 49 patients with HNC and 14 non-oncologic controls recruited between August 2021 and March 2022. Longitudinal follow-up was performed on 25 HNC patients. Plasma antibodies (Abs) against Spike (S1/S2), receptor-binding domain (RBD), and nucleocapsid (NC) of IgG/IgA isotypes and 25 cytokines/chemokines were quantified using MILLIPLEX® technology. The frequency, phenotype, and isotype of circulating SARS-CoV-2-specific B-cells were studied by flow cytometry using RBD tetramers (Tet++). The proliferation of B-cells and CD4+ and CD8+ T-cells in response to Spike/NC peptides was monitored by a carboxyfluorescein succinimidyl ester (CFSE) assay. Results: Plasma SARS-CoV-2 S1/S2/RBD IgG/IgA Abs were detected in all HNC participants at enrollment median time since immunization (TSI) 117 days at levels similar to controls and were significantly higher in convalescent/hybrid versus vaccinated. NC IgG/IgA Abs were only detected after infection. The frequency of Tet++ B-cells, enriched in the CD27+ memory phenotype and IgG/IgA isotype, positively correlated with plasma levels of RBD IgG/IgA Abs and Spike-specific CD4+ T-cell proliferation, regardless of the immunization status and TSI. Spike/NC-specific B-cell proliferation reached the highest levels in convalescent HNC and was positively correlated with NC IgG Abs, but not with the frequency of Tet++ B-cells. Finally, Tet++ B-cell frequencies remained stable between the two subsequent visits (median TSI: 117 versus 341 days), indicating their ability to persist for a relatively long time. Conclusions: This study monitored SARS-CoV-2 humoral/cellular immunity in an HNC cohort relative to non-oncologic participants and demonstrates that SARS-CoV-2-specific B-cells persist beyond 11 months post-immunization. These findings have implications for the management of HNC in the context of SARS-CoV-2 infection and other viral infections.